2020
DOI: 10.1186/s12967-020-02356-2
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of metabolomic dysregulation in Chronic Fatigue Syndrome/Myalgic Encephalomyelitis/Systemic Exertion Intolerance Disease (CFS/ME/SEID)

Abstract: Background: Chronic Fatigue Syndrome/Myalgic Encephalomyelitis/Systemic Exertion Intolerance Disease (CFS/ME/ SEID) is a complex illness that has an unknown aetiology. It has been proposed that metabolomics may contribute to the illness pathogenesis of CFS/ME/SEID. In metabolomics, the systematic identification of measurable changes in small molecule metabolite products have been identified in cases of both monogenic and heterogenic diseases. Therefore, the aim of this systematic review was to evaluate if ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 33 publications
2
26
0
Order By: Relevance
“…Our scoping review included 1161 studies, and although our scope was larger than the 2008 review, there is a clear increase in research in the field. However, our findings echo the conclusions of numerous recent reviews [ 3 , 12 , 15 , 16 , 23 , 27 , 29 ], namely, that our confidence in the evidence is too low to draw conclusions about causal factors. This is due to the preponderance of relatively weak study designs.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…Our scoping review included 1161 studies, and although our scope was larger than the 2008 review, there is a clear increase in research in the field. However, our findings echo the conclusions of numerous recent reviews [ 3 , 12 , 15 , 16 , 23 , 27 , 29 ], namely, that our confidence in the evidence is too low to draw conclusions about causal factors. This is due to the preponderance of relatively weak study designs.…”
Section: Discussionsupporting
confidence: 72%
“…The vastness of the research field on etiological factors reflects the variety of causal hypotheses [ 19 ], and in the past two years alone, numerous systematic reviews have been published examining distinct causal factors such as immunological [ 12 , 16 , 29 ], metabolic [ 15 , 23 ], circulatory [ 27 ], and epigenetic factors [ 3 ]. In 2016, the Research Council of Norway selected the CFS/ME field as the pilot field for a research priority setting partnership strategy, in which patients, next of kin, and related organizations prioritized research questions for commissioned research [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…The pathomechanisms of fatigue in MS are incompletely understood [ 1 , 5 ]. Suggestions are (i) immunological mechanisms such as overexpression of pro-inflammatory cytokines, (ii) metabolic dysregulation, (iii) diffuse axonal damage, (iv) fatigability due to reduced plasticity of the MS brain, or (v) neuropsychological influences [ 6 , 7 , 8 ]. Functional MRI studies revealed different areas of cortical activation in fatigued MS patients as compared to non-fatigued patients, indicating different functional patterns in both groups [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Impaired NK cell cytotoxicity is the most consistently described feature in ME/CFS/SEID [42]. Mitochondrial dysfunction may therefore be a consequence, rather than a primary causative factor, in ME/CFS/SEID [44].…”
Section: Discussionmentioning
confidence: 99%
“…It has been described that these differences make ME/CFS/SEID patients chemically distinguishable from respective HC participants [13]. This is only a small representation of available metabolite studies, a detailed investigation on metabolomic dysregulation in ME/CFS/SEID patients compared to healthy controls has been conducted by Huth et al [44].…”
Section: Discussionmentioning
confidence: 99%